Gamma Irradiation for Agrifood: Non-Destructive Approaches to Study the Secondary Effects Produced in Italian Wheat Matrices - Rocco Carcione; Leonardo Lanzetta; Beatrice D’Orsi; Ilaria Di Sarcina; Emiliana Mansi; Jessica Scifo; Alessia Cemmi (Polysaccharides)
This work investigates the effects of gamma irradiation (0.1–10 kGy) on four Italian wheat matrices, such as durum, conventional soft, integrated soft, and biological soft wheat, by coupling Raman, FTIR-ATR and EPR spectroscopies to provide complementary insights into the structural, conformational, and radical-based transformations occurring in starch, the primary polysaccharide in wheat. As a general trend, gamma irradiation up to 10 kGy does not induce drastic degradation or depolymerization of wheat components. However, deeper investigations reveal that wheat composition is crucial in modulating the effects of gamma irradiation on structural and conformational rearrangements of starch units. Raman and FTIR-ATR spectroscopy analyses showed an increase in random coil fractions, with the most significant changes observed in durum wheat, plausibly attributed to its higher protein content. EPR analyses confirmed a dose-dependent increase in free radicals, with different recombination kinetics between wheat types influenced by their intrinsic composition and molecular organization. The proposed spectroscopic approaches allow for rapid and non-destructive analyses of molecular structure, chemical composition, and free radical content in irradiated wheat matrices with minimal sample preparation. These approaches can be extended in the development of screening methods for a wide range of polysaccharides in a variety of crops.